PENGARUH MOTIVASI, KOMPETENSI TERHADAP KINERJA GURU DIMEDIASI KEPUASAN KERJA (Students' Journal of Economic and Management, 2013)
The purpose of this study was to analyze the influence of motivation, competence on teacher’s performance in Jepara regency with job satisfaction as mediating. This study participated 127 teacher as a sample. The respondent are teacher form SMA Negeri 1 Jepara representated as eks RSBI, SMA Negeri 1 Tahunan representated as central Jepara region, SMA Negeri 1 Pecangaan representated as south Jepara region, dan SMA Negeri 1 Bangsri representated as north Jepara region. Measurement of the instrument using linkert scale 7 answers alternative, with multiple regression as a analyze method. Based on t analyze in this study can be concluded that (1) motivation has the positive and significant impact on teacher’s job satisfaction (2) competence has the positive and significant impact on teacher’s job satisfaction (3) motivation does not affect the teacher’s job performance (4) competence has the positive and significant impact on teacher’s job performance (5) job satisfaction has the positive and significant impact on teacher’s job performance. From the mediation analyze give the information that motivation and competence have indirect effect to teacher’s job performance trough job satisfaction. Keyword : motivation, competence, job satisfaction, teacher’s job performance.